RESPON TERHADAP REGULASI PERKAWINAN DI INDONESIA - Sakirman (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2013)
Based on historical records, the demand to change the rules of marriage in Indonesia from pre-independence till now was initiated by the women’s movement and feminist. These cases had have at the beginning of the 20th century that women’s movement has influenced the world women in the 3rd world. Thus, it have an effect for open the eyes of many people over the oppression of women as a result of the rules of conventional marriage and the need for enforcement of women’s rights.